The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1002/bdm.490
|View full text |Cite
|
Sign up to set email alerts
|

The role of self-esteem and anxiety in decision making for self versus others in relationships

Abstract: Previous research has documented a tendency for people to make more risk-seeking decisions for others than for themselves in relationship scenarios. Two experiments investigated whether this self -other difference is moderated by participants' selfesteem and anxiety levels. In Experiment 1, lower self-esteem and higher anxiety levels were associated with more risk-averse choices for personal decisions but not for decisions for others. Therefore, participants with lower self-esteem/higher anxiety showed greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
75
0
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(91 citation statements)
references
References 46 publications
9
75
0
7
Order By: Relevance
“…Likewise, NSE was significantly negatively related to N (r = -.320, p  .01) while significantly positively related to E (r = .285, p  .01) and L (r = .090, p  .05). In other words, a respondent who reported to have greater self-esteem, higher positive self-esteem, or lower negative self-esteem tended to be less inclined to anxiety and fears (N), but more extroverted (E) and easier to be influenced by others, as found in previous studies (Dalgas-Pelish, 2006;Pepi et al, 2006;Situ & Li, 2007;Stringer & Heath, 2008;Wray & Stone, 2005).…”
Section: Journal Of Second Language Teaching and Research Volume One supporting
confidence: 57%
See 1 more Smart Citation
“…Likewise, NSE was significantly negatively related to N (r = -.320, p  .01) while significantly positively related to E (r = .285, p  .01) and L (r = .090, p  .05). In other words, a respondent who reported to have greater self-esteem, higher positive self-esteem, or lower negative self-esteem tended to be less inclined to anxiety and fears (N), but more extroverted (E) and easier to be influenced by others, as found in previous studies (Dalgas-Pelish, 2006;Pepi et al, 2006;Situ & Li, 2007;Stringer & Heath, 2008;Wray & Stone, 2005).…”
Section: Journal Of Second Language Teaching and Research Volume One supporting
confidence: 57%
“…People with high self-esteem are more creative, and more likely to assume an active role in social groups and to express their views frequently and effectively. Students with greater self-esteem are more likely to be successful academically in school (DalgasPelish, 2006;Ja, Huai, & Guo, 2007;Pepi, Faria, & Alesi, 2006;Rayle, Arredondo, & Kurpius, 2005;Stringer & Heath, 2008), happier (Zhang, 2005), less anxious (Situ & Li, 2007;Wray & Stone, 2005), and to adopt higher quality learning strategies (Watkins, 2000).…”
Section: Self-esteemmentioning
confidence: 99%
“…In the case of responsibility the resulting shift could be in both directions. In the psychological literature, a prominent explanation for a risky shift is the psychological self-other distance (e.g., Beisswanger et al, 2003;Cvetkovich, 1972;Stone and Allgaier, 2008;Trope and Liberman, 2010;Wray and Stone, 2005) in which the evaluation of a potential loss in a risky situation is decreasing in the distance to the decision maker. This nding translates directly to the results from economic experiments (e.g., Harrison, 2006;Laury, 2002, 2005), as risk aversion is signicantly decreased in hypothetical situations without real consequences in the laboratory 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Because the hypersensitivity to negative events and the tendency to worry about negative outcomes are hallmarks of several affective personality traits or disorders like anxiety and depression (Maner & Schmidt, 2006;Mineka et al, 2003;Wray & Stone, 2005), one may assume that performance monitoring may vary with these affective personality traits. Consistent with this hypothesis, several studies have reported an effect of anxiety or depression on the ERN (e.g., Aarts & Pourtois;2010;Holmes & Pizzagalli, 2008;Olvet & Hajcak, 2008).…”
mentioning
confidence: 99%